(untitled) (Swiss Medical Weekly, 2012)
QUESTIONS UNDER STUDY: Deep brain stimulation (DBS) has become a standard therapy for some forms of severe movement disorders and is investigated for other neurological and psychiatric disorders, although many scientific, clinical and ethical issues are still open. We analyse how the Swiss DBS community addresses these problematic issues and future challenges. METHODS: We have performed a survey among Swiss DBS centres and a Delphi study with representatives of all centres and further stakeholders related to the topic. RESULTS: The current DBS infrastructure in Switzerland consists of seven facilities. About 850–1,050 patients have received a DBS system in Switzerland for various indications since its advent in 1976. Critical issues like patient selection and dealing with side effects are in accordance with international standards. There are indications of a conservative referral practice in Switzerland for DBS interventions, but the data available do not allow verifying or refuting this point. CONCLUSIONS: Issues to investigate further are whether or not there is an unmet medical need with respect to DBS, long-term medical and psychosocial sequelae of the intervention, conditions for enhancing the (research) collaboration of Swiss DBS centers, and the effect of the recent decision to reduce the number of DBS centres to 4 (resp. possibly 3) on the potential of this therapeutic approach.